Adverse childhood experiences and adult dental care utilization in the United States: Variation by race and ethnicity - Alexander Testa; Karyn Fu; Dylan B. Jackson; Rahma Mungia; Thomas W. Oates; Jason M. Nagata; Kyle T. Ganson (PLoS ONE, 2025)
Adverse childhood experiences (ACEs) are associated with negative health outcomes, including poorer oral health. While research has shown that ACEs are associated with lower dental care utilization, most studies focus on childhood and adolescence, with limited attention to their long-term impact in adulthood or differences across racial and ethnic groups.. This study examines the relationship between ACE exposure and past-year dental care use in adulthood and assesses racial/ethnic differences in this association. Using data from the 2020 Behavioral Risk Factor Surveillance System (BRFSS), we analyzed a sample of 88,728 adults from 21 states and the District of Columbia. The primary outcome was any past-year dental care use. ACEs were summed into a composite score. Multivariable logistic regression models assessed the relationship between ACEs and past-year dental care use, with multiplicative interaction terms used to examine racial/ethnic differences in the observed association. Overall, 63.2% of adults reported any past-year dental care use. Higher ACE exposure was associated with lower odds of dental care use (adjusted odds ratio [aOR] = 0.95, 95% CI: 0.93–0.97, p < .001). The negative association between ACEs and dental care use was strongest for non-Hispanic White respondents, whereas the relationship between ACEs and dental care was attenuated for non-Hispanic Black and Hispanic respondents. These findings expand knowledge on the association of ACEs with dental care use in adulthood and how this relationship may vary across the population.